KEPASTIAN HUKUM PUTUSAN ARBITRASE DALAM KONTEKS PEMBATALAN DITINJAU DARI ASAS FINAL AND BINDING - Popy Nurjanah; Wira Franciska; Nur Hakim (SINERGI : Jurnal Riset Ilmiah, 2026)
Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution stipulates that arbitration awards are final and binding. This nature is a manifestation of legal certainty. Final means the last, while binding means that the disputing parties are legally bound from the moment the award is pronounced to implement the arbitration award. However, the same law also regulates the annulment of arbitration awards that are final and binding. Parties who are dissatisfied with an arbitration award use the grounds for setting aside an arbitration award to avoid their obligations under the arbitration award. Such actions will certainly cause legal uncertainty for arbitration awards. The method used in this study is normative legal research conducted as an effort to obtain the data needed in relation to the problem. The primary data used in this study are laws and regulations and court decisions. The secondary legal data used are books/literature and journals. Meanwhile, the tertiary legal data are derived from general dictionaries and legal dictionaries. All data were then analyzed using qualitative legal analysis methods. Since the issuance of Constitutional Court Decision Number 15/PUU-XII/2014 on November 11, 2014, the grounds for annulment of an arbitration award no longer need to be proven by a court decision. Court judges are given the discretion to assess the existence of document forgery, document concealment and/or deception. The legal certainty of arbitration awards, which are final and binding, must be maintained. The annulment of arbitration awards as regulated in Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution must be interpreted as an effort to ensure that arbitration awards remain final and binding. Annulment is not an attempt to avoid obligations that have been decided. The role of the Court is also very important in maintaining the finality of arbitration awards. The Court must be able to issue decisions that have clear legal consequences for arbitration awards.